A Modified TOPSIS Method Based on D Numbers and Its Applications in Human Resources Selection. (5th July 2016) - Fei, Liguo; Hu, Yong; Xiao, Fuyuan; Chen, Luyuan; Deng, Yong
Abstract : Multicriteria decision-making (MCDM) is an important branch of operations research which composes multiple-criteria to make decision. TOPSIS is an effective method in handling MCDM problem, while there still exist some shortcomings about it. Upon facing the MCDM problem, various types of uncertainty are inevitable such as incompleteness, fuzziness, and imprecision result from the powerlessness of human beings subjective judgment. However, the TOPSIS method cannot adequately deal with these types of uncertainties. In this paper, aD -TOPSIS method is proposed for MCDM problem based on a new effective and feasible representation of uncertain information, calledD numbers. TheD -TOPSIS method is an extension of the classical TOPSIS method. Within the proposed method, D numbers theory denotes the decision matrix given by experts considering the interrelation of multicriteria. An application about human resources selection, which essentially is a multicriteria decision-making problem, is conducted to demonstrate the effectiveness of the proposedD -TOPSIS method.